Kualitas Pelayanan Publik Terhadap Indeks Kepuasan Masyarakat Di Puskesmas Rappang - ika fitria; Muhammad Arisal Asad; Lukman Lukman (PRAJA: Jurnal Ilmiah Pemerintahan, 2020)
Determine the quality of public services at the Rappang Puskesmas, to determine the community satisfaction index at the Rappang Puskesmas, and to determine the effect of the quality of public services on the community satisfaction index at the Rappang Puskesmas. The method used in this research is quantitative descriptive approach. The population in this study was 4983 people who have been counted as patients registered at the health center since 2019-2020. The sampling technique used was Random Sampling using the Slovin formula so that a sample of 98 people was obtained. Data collection techniques are carried out using questionnaires, observation and literature study. The collected data is then processed using a quantitative descriptive analysis technique with the help of SPSS 21.0 with a measurement scale using a Likert Scale. The results showed that the quality of service at the Rappang Puskesmas was in the poor category with an average percentage of 56.8%, the community satisfaction index at the Puskesmas Rappang was in the poor category with an average percentage of 60%, and the effect of the quality of service on community satisfaction index with a percentage of 55.7% influential.